2006
DOI: 10.1002/ccd.20689
|View full text |Cite
|
Sign up to set email alerts
|

Carotid stenting with distal protection in high surgical risk patients: The BEACH trial 30 day results

Abstract: The similarity in periprocedural event rates for the Pivotal and Roll-in groups suggests a flat learning curve for experienced operators using this carotid stent system. The similarity in event rates for the Bilateral group, when compared with the Roll-in and Pivotal groups, suggests that staged sequential treatment of bilateral stenoses may be performed at the same risk as for unilateral lesions. The 30-day safety of this stent and distal emboli protection system is encouraging and compares favorably with oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
1
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(129 citation statements)
references
References 13 publications
7
112
1
9
Order By: Relevance
“…9,17,26,27 The reported rate of severe bilateral carotid stenosis and/or occlusion varies widely (3.2%-39%) 8,9,17,28 and was encountered in 14.6% of the patients at high surgical risk in our prospective CAS data base. Although bilateral carotid stenosis has been shown to potentially increase the risk for complications during CEA or CAS and has been included as 1 of the high risks for CEA, our data revealed that there was no significant difference in outcome at 30 days or at 6 months between the bilateral and unilateral stent-placement patient groups.…”
Section: Discussionmentioning
confidence: 90%
“…9,17,26,27 The reported rate of severe bilateral carotid stenosis and/or occlusion varies widely (3.2%-39%) 8,9,17,28 and was encountered in 14.6% of the patients at high surgical risk in our prospective CAS data base. Although bilateral carotid stenosis has been shown to potentially increase the risk for complications during CEA or CAS and has been included as 1 of the high risks for CEA, our data revealed that there was no significant difference in outcome at 30 days or at 6 months between the bilateral and unilateral stent-placement patient groups.…”
Section: Discussionmentioning
confidence: 90%
“…7 All patients were at high medical and surgical risk for carotid endarterectomy. [8][9][10] The major eligibility criteria for high-risk patients are listed in Table 1. All patients were required to have at least one coexisting condition that potentially increased the risk posed by carotid endarterectomy.…”
Section: Methodsmentioning
confidence: 99%
“…The use of the FilterWire DPD has been previously reported, 3,8 and shortterm outcomes of a randomized trial have been published. 27 In an ex vivo human atherosclerotic CA preparation, 100% of particles Ͼ 360 m in diameter and 93% of particles Ͼ 80 m in diameter embolized following balloon angioplasty and stent placement were captured successfully by this DPD. 16 …”
Section: The Filterwire Ex Distal Protection Devicementioning
confidence: 96%